Clinical outcomes among patients with head and neck cancer treated by intensity‐modulated radiotherapy with and without adaptive replanning. Issue 11 (22nd January 2014) - Chen, Allen M.; Daly, Megan E.; Cui, Jing; Mathai, Mathew; Benedict, Stanley; Purdy, James A.
Abstract Background The purpose of this study was to determine the effect of adaptive replanning on clinical outcome among patients treated by intensity‐modulated radiotherapy (IMRT) for head and neck cancer. Methods Three hundred seventeen patients underwent IMRT with daily image‐guidance for newly diagnosed squamous cell carcinoma of the head and neck to a median dose of 66 Gy (range, 60–74 Gy). Of these 317 patients, 51 (16%) underwent adaptive radiotherapy with modification of the original IMRT midway during treatment. Results The 2‐year local‐regional control was 88% for patients treated with adaptive replanning compared with 79% for patients treated without (p = .01). The median time to local‐regional recurrence for the 4 patients treated by adaptive radiotherapy was 7 months (range, 3–15 months) with all failures occurring within the high‐dose planning target volume (PTV). Conclusion Although the use of routine replanning is probably not necessary, our findings do suggest a significant benefit in appropriately selected patients. © 2014 Wiley Periodicals, Inc. Head Neck 36: 1541–1546, 2014